The impact of TV mass media campaigns on calls to a national quitline and the use of prescribed nicotine replacement therapy: a Structural vector autoregression analysis - Haghpanahan, Houra; Mackay, Daniel F.; Pell, Jill P.; Bell, David; Langley, Tessa; Haw, Sally (Wiley, 2017)
Aims: To estimate 1) the immediate impact; 2) the cumulative impact; and 3) the duration of impact of Scottish tobacco control TV mass media campaigns (MMCs) on smoking cessation activity, as measured by calls to Smokeline and the volume of prescribed nicotine replacement therapy (NRT).